2020
DOI: 10.1016/j.ijcha.2019.100457
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular filling pressure in Tetralogy of Fallot: Correlation between invasive and noninvasive indices

Abstract: BackgroundLeft heart filling pressures, as measured by pulmonary artery wedge pressure (PAWP), is associated with heart failure related mortality. Because of the prognostic importance of PAWP, several echocardiographic indices have been proposed for noninvasive assessment of PAWP. However, these indices have not been validated in the congenital heart disease population. The purpose of this study was to determine the correlation between echocardiographic indices of PAWP, and the effect of high PAWP on transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…As long-term survival with rToF is improving, the importance of understanding the hemodynamics of these congenital heart defects become apparent [ 16 ] while timing of PVR after initial surgical correction remains debated [ 17 ]. A better understanding of the intrinsic relationship between the left and right sides of the heart in rToF and the importance of intracardiac pressures [ 18 ] will aid in developing non-invasive measurements and to guide future therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As long-term survival with rToF is improving, the importance of understanding the hemodynamics of these congenital heart defects become apparent [ 16 ] while timing of PVR after initial surgical correction remains debated [ 17 ]. A better understanding of the intrinsic relationship between the left and right sides of the heart in rToF and the importance of intracardiac pressures [ 18 ] will aid in developing non-invasive measurements and to guide future therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In concordance with these findings, we found that LA compliance was the best predictor of h-LTA. Normalizing LA strain to estimated filling pressures ( E / e ′) may be more acurate to detect elevated filling pressure in the specific population of cTOF in whom standard parameters were reported to be less performant compared to general population ( 35 ). Our findings are in keeping with previous studies having demonstrated the potential interest of another combined echocardiographic parameters including LA stiffness estimated with the ratio ( E / E ′)/LAS ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, there is a growing body of evidence on the importance of precisely evaluating LV function and LV filling pressures in c-ToF. Egbe et al found indexed LA volume to have a moderate discriminatory ability to dectect LV elevated pressure and demonstrated that most of the echocardiographic indices endorsed by the practice guidelines ( 35 ) had very poor performance in the assessment of left heart filling pressures in the c-TOF population. The use of other echocardiographic indices for evaluating LV filling pressure therefore appears necessary in this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been reported in other forms of congenital heart disease, such as tetralogy of Fallot and coarctation of the aorta. [24][25][26] It should be noted that the cut-off value of >15 mm Hg may be insensitive for otherwise young healthy adults, and thus the prevalence of underlying increase in left filling pressures might have been underestimated. There was a lower prevalence of ≥moderate RV dysfunction in patients with abnormal PAWP.…”
Section: Left-sided Disease and The Role Of The Truncal Valvementioning
confidence: 99%